Dynamic variation of bacterial community assemblage and functional profiles during rice straw degradation - Sun, Ruibo; Wang, Xin; Alhaj Hamoud, Yousef; Lu, Mengxing; Shaghaleh, Hiba; Zhang, Wenjie; Zhang, Chaochun; Ma, Chao (Frontiers in Microbiology, 2023)
Bacteria is one of the most important drivers of straw degradation. However, the changes in bacterial community assemblage and straw-decomposing profiles during straw decomposition are not well understood. Based on cultivation-dependent and independent technologies, this study revealed that the “common species” greatly contributed to the dynamic variation of bacterial community during straw decomposition. Twenty-three functional strains involved in straw decomposition were isolated, but only seven were detected in the high-throughput sequencing data. The straw decomposers, including the isolated strains and the agents determined by functional prediction, constituted only 0.024% (on average) of the total bacterial community. The ecological network showed that most of the identified decomposers were self-existent without associations with other species. These results showed that during straw composition, community assembly might be greatly determined by the majority, but straw decomposition functions might be largely determined by the minority and emphasized the importance of the rare species in community-specific functions.